(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Knowledge is a major advantage for achieving human development in any country. Knowledge is achieved through the number of years of schooling. The cognitive variables represented in the number of graduates from high school, graduates from university studies, and graduates from postgraduate studies as independent explanatory variables, and GDP as a dependent variable in Iraq During the period (2005-2020), internal growth theories emphasize the importance of human capital and knowledge in providing a logical explanation for the development achieved in countries that possess natural resources. The researchers relied on the (ARDL) methodology, because the variables are stable in different degrees, based on the Dickey test. Fuller to reveal the unit root in the model, and the results confirmed the existence of a causal relationship between the GDP and the knowledge variables, and the relationship was from one direction of the GDP to the knowledge variables, and the opposite was not achieved, and the study proved that the independent variables are influential and significant in economic activity.